Adapting to climate change: Forecasts for a fairer future - Kamau, Sharon W. (Technical Centre for Agricultural and Rural Cooperation, 2011)
A system delivering weather details via SMS to farmers in Kenya makes use of traditional and modern forecasting methods, alerting them to periods of heavy rain or drought.